Consumption Value dan Pengaruhnya terhadap Minat Pembelian Produk Local Brand - Wijayanti, Rena Feri; Budiarti, Lina; Pribadi, Joni Dwi; Lova, Evy Fajriantina; Oktora, Yekie Senja; Kusumasasti, Ika (SENTRI: Jurnal Riset Ilmiah, 2025)
The development of beauty products in Indonesia shows impressive growth. One example is the growth of local brand beauty products. The growth of beauty products demonstrates the potential for consumption, as consumers consider beauty products a necessity that continues to attract purchase interest. This study aims to analyze the consumption value of local brand product purchase interest. This study used a quantitative approach. The population consists of Malang residents familiar with local beauty products. The sample size was 128 respondents, drawn through purposive sampling techniques. Data collection was conducted through questionnaires. Validity and reliability tests used in this study showed that the questionnaire items used were valid and reliable. Subsequent tests were conducted, including the Classical Assumption test, multiple linear regression tests, and partial and simultaneous hypothesis testing. Based on the results of the data analysis, it was found that functional value and conditional value did not have a significant effect. In contrast, emotional value, social value, and epistemic value had a significant effect. The findings open up opportunities for further research to explore the same product category in more depth or expand the scope to other product categories, thereby providing a more varied picture.